Strategic Management Analysis of Indonesian Sharia Banking - Ridwan, Wawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Increasing banking competition on a national and global scale requires managers to determine the right strategic steps. This is done to improve banking performance as a public entity which is increasingly needed. The purpose of this study is to analyze the strategic management of Indonesian Islamic banking in increasing market share in the Indonesian banking industry. This study uses the literature study method and uses secondary data as well as providing explanations and analysis of various literature studies and secondary data related to the strategic management process of Indonesian Islamic banking. The results of this research, analysis of the external environment of Indonesian Islamic banking found several opportunities to encourage the competitiveness of the Islamic banking industry but also found threats from competition from conventional banking. From the analysis of the internal environment, several weaknesses were found, namely, in the field of human resources, information technology, and the number of bank branch offices. By analyzing the external and internal environment, medium and long-term goals and objectives of Islamic banking are produced and several strategies are produced, namely, expansionary strategy, conventional bank conversion strategy to Islamic banking, human resource strategy, banking technology development strategy, funding, and capital strategy, and a strategy to increase the number of bank offices. From the analysis of the internal environment, several weaknesses were found, namely, in the field of human resources, information technology, and the number of bank branch offices.